In situ examination of handwritten blue ballpoint inks using video spectral comparison with chemometrics - Sauzier, Georgina; McGinn, J.; Trubshoe, T.; Lewis, Simon (2019)
Video spectral comparator (VSC®) workstations are routinely used for visual examinations of pen inks on handwritten documents. Current VSC® models also permit spectral acquisition, which can be combined with chemometric techniques to statistically determine ink similarity. However, there is a lack of research comparing such an approach to typical examinations by forensic experts. This preliminary study compares the analysis of handwritten blue ballpoint inks using visual and spectroscopic analysis. Both approaches were successful in detecting simulated additions or alterations on paper documents. These approaches could thus complement each other as an integrated workflow; providing quantitative data to support expert opinions.